Detecting Intestinal Malrotation on Hepatobiliary Scintigraphy: Making a Case for a Better Standardized Reporting Template. (April 2018) - Miner, Lane T.; Tulchinsky, Mark
Abstract : Abstract: Intestinal malrotation displays classic pattern of the small bowel activity on hepatobiliary scintigraphy that could lead to the diagnosis, but only if an interpreting physician looks for it. Presented are 2 cases, one demonstrates diagnostic findings during the first 60-minute phase, whereas the other reveals the diagnosis only on the later sincalide stimulation phase. The currently recommended structured reporting for hepatobiliary scintigraphy does not include examination of bowel activity pattern, which could result in a missed diagnosis. Including interrogation of the small bowel pattern into the structured reporting checklist would ensure consistent detection of this rare but most consequential diagnosis.